ON NEAR EQUITABLE TOTAL DOMINATION IN GRAPHS - DEVI, S. MEENA; JANAKI*, S. (International Journal of Mathematical Archive, 2018)
In this paper, we initiate a study on new domination parameter near equitable total domination number of a graph. We defined total domination and near equitable total domination in graphs. The minimal near equitable total dominating sets are established. Compute for some standard graphs. The relation between and are obtained. Also, characterization is given for near equitable total domination set is minimal.